2003
DOI: 10.1111/j.1582-4934.2003.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiomolybdate anticopper therapy for Wilson's disease inhibits angiogenesis, fibrosis and inflammation

Abstract: The need for agents to lower body copper in Wilson's disease, a disease which results from copper toxicity has been the driving force for the development of the effective anticopper drugs penicillamine, trientine, zinc, and now tetrathiomolybdate (TM). Because of its rapid action, potency, and safety, TM is proving to be a very effective drug for initial treatment of acutely ill Wilson's disease patients. Beyond this, TM has antiangiogenic effects, because many proangiogenic cytokines require normal levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 72 publications
0
58
2
1
Order By: Relevance
“…We did not find any effect of zinc on the serum cytokine levels, although it is reported to increase serum levels of cytokines in literature. Our findings did not support the views of Brewer et al [11]. Serial analysis of cytokines before and after initiating treatment may establish the relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find any effect of zinc on the serum cytokine levels, although it is reported to increase serum levels of cytokines in literature. Our findings did not support the views of Brewer et al [11]. Serial analysis of cytokines before and after initiating treatment may establish the relationship.…”
Section: Discussioncontrasting
confidence: 99%
“…In 1980, it was first noticed that Cu played an important role in angiogenesis [23]. In normal adult tissues, there is no action of angiogenesis except for wound healing, inflammatory reaction or the menstrual cycles [24]. Tumors are dependent on angiogenesis for their growth, invasion and metastasis, a novel concept proposed by Dr Folkman in 1971 [25,26].…”
Section: Role Of Cu In Angiogenesis and Cancer Progressionmentioning
confidence: 99%
“…In particular, it has been shown that TM can sequester copper from several metallo-chaperones/ligands (e.g. ATOX1, ceruloplasmin, bovine serum albumin and metallothioneins), and interfere with their function in the regulation of angiogenic pathways [244,245]. Moreover, in vitro assays demonstrated that ATN-224 inhibits endothelial activation, migration and sprout formation by regulating several genes involved in angiogenesis, ion binding and inflammatory processes [246].…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%